La filosofia del dialogo di Guido Calogero - Pagano, Maurizio (Premio Ricerca «Città di Firenze», 2012)
Centred around the topic of dialogue, the philosophical position which Guido Calogero (1904-1986) came to hold at the beginning of the 1950s, and developed in his subsequent studies, establishes a complex relationship with the philosophical research from the years before, interested in the historical origins of the logical and gnoseological problems in ancient thought and their necessary dissolution in contemporary idealism. This work highlights how these bonds condition the formulation of the dialogic principle, despite the philosopher's intention to assert its speculative autonomy; but it also shows, at the same time, how this renewed ethical criterion enriches Calogero's position, opening it to developments that contemporary reflection can acquire and investigate further.